UNDANG-UNDANG CIPTA KERJA DALAM PERSPEKTIF PEMIKIRAN PHILIPPE NONET AND PHILIP SELZNICK MENGENAI HUKUM KONSERVATIF - Ali Dahwir (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2020)
An omnibus law from early to serious debate with the community and interest groups , in the end are passed by the house of representatives through a meeting quickly. The meeting quickly led to rejection 2 factions in the house of representatives against the law no. 11 years 2020 about copyright, work the Democrat Faction and FKPS. Community groups concerned with this law also launch a wave of protests and rejected the law firm. One of the evidence is a process of discussion and the adoption of the law are not transparent and accountable, also did not involve elements of society. Depart from the reality, later writers try collaboration these phenomena in perspective thought phillippe nonet and philip selznick, conservative of the law in the process, it is not transparent, and accountable if there are involving public in his discussion, but only. formality. By using the method normative juridical based on a source of reference contextual , the author concluded that related to endorsement ciptaker this law that the government too rash that disregarded asean legislation regulation should transparent , accountable , prudence , and participatory .As stipulated in law no. 15 years 2019 revision of the law no. 12 years 2011 on the establishment of legislation regulation